The purpose Pengaruh Budaya Organisasi, Stress Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan Pada PT. Central Satrya Perdana: Organizational Culture, Work Stress, Compensation - Fx.Pudjo Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
The purpose of this study is to determine how much influence partially and simultaneously the independent variables have on the dependent variable. The sample used was simple random sampling. Questionnaires distributed to respondents amounted to 100 people. Statistical data analysis used reliability, validity, normality, autocorrelation, multicollinearity heteroscedasticity, coefficient determination, individual test (t-test) and joint test (f-test), with the SPSS 25 statistical tool. The t-test results showed independent The good variable partially has a positive and significant influence on the dependent variable with the results obtained that the t value for work discipline is greater than 10,952. ( > ) t table is 1,966 and the probability is .0000 is smaller (< ) 0.05, the t value for work stress is 5.138 greater. ( > ) t table 1.966 and the probability 0000 is smaller (< ) 0.05 and the t value for compensation is 2.996. greater .( > ) ttable 1,996 and .0004 probability smaller (< ) 0.05. The results of F arithmetic = 252.007 probability value = 0.000 then F arithmetic > F table (252.007 greater (>) 3.09 probability value 0.000 smaller (<) 0.05, simultaneously has a positive relationship and has an effect on the dependent variable on employee productivity and value The coefficient of multiple determination of R2 is 88.4% of the productivity explained by the independent variable factors and the remaining 100%-88.3% = 16.7% excluding the independent factors. Keywords: Organizational Culture, Work Stress, Compensation